Perbedaan Varian Waktu Puasa Terhadap Nilai Glukosa Darah Puasa 8 Jam, 10 Jam dan 12 Jam Pada Pasien Glaukoma Di RSU Bunda Jembrana - Oki wibawa putra oki; Anak Agung Eka Cahyani; Diah Prihatiningsih (Politeknik Kesehatan Kementerian Kesehatan Banten, 2025)
Blood glucose level is a term that refers to the level of glucose in the blood. Blood glucose levels increase after meals and are at their lowest in the morning before meals. This study aimed to determine differences in fasting time variations in 8-hour, 10-hour, and 12-hour fasting blood glucose values in glaucoma patients at Bunda Jembrana General Hospital. This study is a quasi-experimental study. The population used in this study was all glaucoma patients at Bunda Negara General Hospital. The sampling technique used in this study was probability sampling using proportionate stratified random sampling. Data collection in this study was conducted through primary data collection. The data were obtained from fasting blood glucose tests on 40 respondents, selected from glaucoma patients. Each respondent underwent three fasting sessions: 8 hours, 10 hours, and 12 hours, resulting in 120 data points. The examination was conducted using a spectrophotometer. The data analysis technique used in this study is the ratio data scale. The data were normally distributed with the one sample Kolmogorov-Smirnov test. The results of the study showed that the average 8-hour blood glucose level of glaucoma patients was 171.8 mg/dl, the average 10-hour blood glucose level of glaucoma patients was 165.1 mg/dl, and the average 12-hour blood glucose level of glaucoma patients was 160.1 mg/dl with a difference in the average 8-hour, 10-hour and 12-hour blood glucose levels of glaucoma patients of 7.8 mg/dl (19.5%). The SPSS Anova Multiple Comparisons test showed that there was a significant difference between the fasting blood glucose levels of 8 hours, 10 hours and 12 hours in glaucoma patients.